Arterial missile embolism following penetrating chest trauma: a case report - Fourie, Nadia M.; Wineberg, Devorah (International Surgery Journal, 2026)
Missile embolism is a rare but potentially serious complication of penetrating trauma that occurs when a projectile enters the vascular system and migrates within the circulation. Although described in military literature, civilian reports remain limited. A 25-year-old male presented following a gunshot wound to the left chest and arm. He was haemodynamically stable on arrival. Initial radiography demonstrated a bullet in the posterior mediastinum with a small haemothorax. Extended focussed assessment with sonography for trauma revealed a small pericardial effusion. Computed tomography performed shortly thereafter demonstrated migration of the projectile to the level of the aortic bifurcation, consistent with arterial missile embolism. The patient was transferred for cardiothoracic evaluation due to a suspected cardiac injury, which was managed non-operatively. Following transfer back to our institution, angiography confirmed the bullet lodged at the aortic bifurcation. Endovascular retrieval was attempted but was unsuccessful due to projectile deformation. Open arteriotomy was subsequently performed allowing successful bullet removal and arterial repair with a vein patch. The patient recovered postoperatively and was discharged after several days. Missile embolism is an uncommon but important diagnosis following penetrating trauma. Early imaging and high index of suspicion are critical, particularly when projectile location is incongruent with the expected wound trajectory. Multidisciplinary management is essential to optimize outcomes.